2009
DOI: 10.1080/17458080902929895
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of magnetic properties on crystallite size of CoFe2O4nanoparticles synthesised by auto-combustion method

Abstract: Cobalt ferrite (CoFe 2 O 4 ) nanoparticles were prepared through an auto-combustion method. The results of XRD show that the crystallite size of CoFe 2 O 4 nanoparticles increases from 57 to 105 nm with a slight change in lattice constant as the annealing temperature increases from 300 to 1200 C. The magnetic measurements by vibrating sample magnetometer (VSM) show that M s increases monotonously by increasing the annealing temperature from 300 to 1200 C and C hB and M s reached a maximum when annealing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Cobalt nitrate (Co(NO 3 Á H 2 O into 300 mL distilled water. The precursor was obtained by heating the solution till the occurrence of combustion, which was followed by the annealing treatment in air at 400 1C for 4 h (previous work has shown that CoFe 2 O 4 prepared through this method has the maximum coercivity) [22]. The soft ferrite, Fe 3 O 4 used for the composite, was of analytical grade and was procured commercially (Sinopharm Chemical Reagent Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…Cobalt nitrate (Co(NO 3 Á H 2 O into 300 mL distilled water. The precursor was obtained by heating the solution till the occurrence of combustion, which was followed by the annealing treatment in air at 400 1C for 4 h (previous work has shown that CoFe 2 O 4 prepared through this method has the maximum coercivity) [22]. The soft ferrite, Fe 3 O 4 used for the composite, was of analytical grade and was procured commercially (Sinopharm Chemical Reagent Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…The band observed at 1635 cm À 1 in both samples is assigned to the stretching and bending vibration of the H-O-H bond respectively [53,54]. This shows the physical adsorption of H 2 O on the surfaces.…”
Section: Ft-ir Studiesmentioning
confidence: 98%
“…Therefore, investigations on the synthesis procedures of inorganic salts such as lead oxalate nanoparticles are necessary to produce their powders with controlled particle size, shape, and size distribution [8,9]. Several methods currently have been applied to synthesize inorganic salts nanoparticles such as hydrothermal synthesis [10,11], chemical precipitation [12], template synthesis [13,14], sol-gel [15], emulsion system [16], combustion technique [17], micronization via supercritical fluids technology [18,19], electrochemical processes [20,21], and ultrasonic assisted synthesis [22]. Among these methods, in this study, the chemical precipitation method with a semi-batch reactor was used; because this technique is relatively simple to obtain the particles in powder form and allows us to control the morphology of the product particles [23,24].…”
Section: Introductionmentioning
confidence: 99%